Introduction to hospitality - Walker, John R., 1944- (Prentice Hall, 1999)
This is a comprehensive tour through the fascinating and challenging related fields in the hospitality industry: travel and tourism, lodging, food sservice, meetings, conventions and expositions, leisure and recreation.